Pricing Mechanism in Panyabungan Tradisional Market Viewed from Islamic Economic Perspective - Lubis, Rini Hayati (Department of Sharia Economic Law, Faculty Sharia and Law, UIN Sunan Gunung Djati Bandung, 2024)
This study analyzes the pricing mechanism in the Panyabungan traditional market using the perspective of Islamic economics. The Panyabungan tradisional market is the focus of research because it is the local economic center of the Muslim community. Using a qualitative approach, data is collected through observation and interviews with traders and sellers as well as market stakeholders. The results of the study show that the pricing mechanism in the Panyabungan Old Market is largely based on market forces, which is not in accordance with Islamic economic principles that emphasize fairness in prices. In the traditional market of Panyabungan, there is still intransparency related to prices, price increases at certain moments that are not affected by the substance of the availability of goods, and buying and selling credit without paying attention to sharia principles. The implications of this study reinforce the importance of understanding and applying Islamic economic principles in traditional market practices to achieve the goals of economic justice and sustainability at the local level.